Estimation Normal Vector of Triangular Mesh Vertex by Angle and Centroid Weights and its Application - Yueping Chen; Jian Gao; Hao Wen; Xin Chen (Institute of Advanced Engineering and Science, 2013)
To compute vertex normal of triangular meshes more accurately, this paper presents an improved algorithm based on angle and centroid weights. Firstly, four representational algorithms are analyzed by comparing their weighting characteristics such as angles, areas and centroids. The drawbacks of each algorithm are discussed. Following that, an improved algorithm is put forward based on angle and centroid weights. Finally, by taking the deviation angle between the nominal normal vector and the estimated one as the error evaluation standard factor, the triangular mesh models of spheres, ellipsoids, paraboloids and cylinders are used to analyze the performance of all these estimation algorithms. The machining and inspection operations of one mould part are conducted to verify the improved algorithm. Experimental results demonstrate that the algorithm is effective. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2340